1988
DOI: 10.1598/rrq.23.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Reading and How Children Spend Their Time Outside of School

Abstract: Few studies have provided precise data on how much reading school children do.Fewer still have examined the relation between amount of reading and reading achievement. In the studies reported here, 155 fifth graders wrote down every day on activity forms how many minutes they spent on a wide range of out-ofschool activities. Forms were completed for periods ranging from 8 to 26 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
451
2
30

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(512 citation statements)
references
References 7 publications
29
451
2
30
Order By: Relevance
“…Extensive reading materials provide substantial linguistic input (Bell, 1998) Many studies have shown that extensive reading has positive effects on a variety of students' language skills. Anderson, Wilson, and Fielding (1988) found a correlation between extensive reading and reading ability among children, and a study by Greenberg, Rodrigo, Berry, Brinck, and Joseph (2006) attained similar results with adult learners. Lee's study (2008) with children in Taiwan on sustained silent reading reveals that the longer students read, the better the reading results.…”
Section: Extensive Readingmentioning
confidence: 59%
“…Extensive reading materials provide substantial linguistic input (Bell, 1998) Many studies have shown that extensive reading has positive effects on a variety of students' language skills. Anderson, Wilson, and Fielding (1988) found a correlation between extensive reading and reading ability among children, and a study by Greenberg, Rodrigo, Berry, Brinck, and Joseph (2006) attained similar results with adult learners. Lee's study (2008) with children in Taiwan on sustained silent reading reveals that the longer students read, the better the reading results.…”
Section: Extensive Readingmentioning
confidence: 59%
“…There is good evidence that children and adolescents who engage more often in reading activities have better literacy skills (Anderson, Wilson & Fielding, 1988;Cunningham & Stanovich, 1991;1997;Guthrie et al, 1999;Leppanen, Aunola & Nurmi, 2005;McBride-Chang, Manis, Seidenberg, Custodio & Doi, 1993;Mol & Bus, 2011); however some types of reading activities have been more consistently associated with reading skill. For example, Anderson et al (1988) found that time spent reading books was more strongly associated with reading comprehension and reading speed than other text types (e.g., comics, newspapers and magazines).…”
Section: Reading Frequency and Reading Habitsmentioning
confidence: 99%
“…Although the specific reading challenges faced by students performing below basic level are no doubt heterogeneous, a ubiquitous issue mentioned by their teachers and confirmed by assessment is their limited vocabularies. It is not surprising that the many language minority students in urban districts show gaps in English vocabulary, but even native English speakers may fail to develop rich vocabularies if they have a history of low reading ability, limited comprehension, and low investment of time in reading, because much sophisticated vocabulary is acquired through reading (Anderson, Wilson, & Fielding, 1988;Stanovich, 1986).…”
mentioning
confidence: 99%